Effect of deformation temperature on microstructure and corrosion properties of hot-compressed 347H stainless steel - Qiushuang Wang; Ruidong Li; Junchen Li (Electrochemistry Communications)
The corrosion resistance of 347H stainless steel after hot rolling or hot extrusion has always been a focus of attention in the thermoelectric field. This work uses electrochemical evaluation methods to study the corrosion behavior of 347H stainless steel after hot compression under different temperatures. The effects of dynamic recrystallization (DRX), grain size, and grain boundary (GB) on the corrosion behavior of the material were analyzed by microstructure detection. It is found that 347H stainless steel undergoes a valley stage of corrosion properties when deformed near 1050 ℃ with a constant strain rate. The changes of grain boundary density and Σ3 boundaries caused by deformation at different temperatures are the fundamental reasons for the fluctuation of corrosion properties. These results indicate that deformation temperature is an important factor controlling the corrosion resistance of hot- compressed 347H stainless steel. This study has important reference value for the development of hot deformation technology and the improvement of corrosion resistance of 347H stainless steel.